Unintentional Fall-Related Mortality among the Elderly in Serbia: Importance of Death Reporting Quality - Konstansa Lazarevic; Miodrag Stojanovic; Dragan Milic; Zana Dolicanin; Ljiljana Stosic; Sasa Milicevic; Dragan Bogdanovic (Tehran University of Medical Sciences, 2022)
Background: Falls have been one of the leading causes of injury-related deaths among the elderly, having an increasing trend in many countries. We investigated trends of fall-related mortality among people aged ≥65 yr in Serbia. Methods: Based on official data, we calculated unintentional fall-related mortality rate (MR) from 1998 to 2017, using join point regression analysis to determine annual percentage changes (APC). Starting from 2005, doctors from Serbian Public Health Institute have been controlling the quality of death certificates. Results:  In the 1998-2004 period, MR decreased in men and women aged 65-74 and men aged ≥85 (by -12.4; -13.0; and -15.1% yearly) followed by an upward trend in men and women aged 65-74 (by 76.3 vs.40.2%yearly) from 2004 to 2007 and men aged ≥85 (by 13.7% yearly) from 2004 to 2017. MR decreased among women aged ≥85 (by-9.8% yearly) from 1998 to 2008 and then increased (by 9.0% yearly) from 2008 to 2017. In men and women aged 75-84, an increase of MR (by 7.4 vs.3.1%) was observed during the entire study period. In all age groups, except women aged ≥85, significant negative correlation was found between fall-related deaths and ill-defined and unknown causes of deaths. Conclusion:  Control of death certificates by physicians from the Institute of Public Health led to the better reporting of the increasing trend of fall-related mortality among the elderly. Policy makers must investigate risk factors for fall and then adopt national guidelines for prevention and treatment of fall-related injury.